Seni Pertunjukan Sebagai Alat Pemberdayaan Masyarakat: Studi Kasus Implementasi di Tana Toraja - Jayusman, Monalisa Putri; Untung, Untung; Natsir, Nasrah; Rahmawati, Rahmawati; Gaffar, Fatmawati (JAPPA: Jurnal Andragogi Pedagogi dan Pemberdayaan Masyarakat, 2025)
The aim of this research is to describe the implementation of performing arts as a tool for community empowerment in Tana Toraja. This research uses a qualitative approach with a case study type of research. The subjects of this research are the Tana Toraja government, artists, and local residents of Tana Toraja. Data collection was carried out using interviews, observation and documentation methods. The techniques used in data analysis are data reduction, data presentation and drawing conclusions. Triangulation is used to explain the validity of the data by using source triangulation. Based on the research results, it shows that one of the tools for community empowerment is performing arts. The context that includes Performing Arts is 1) Musical Arts in the form of traditional musical instruments and traditional songs., 2) Dance Arts in the form of ceremonial dance, entertainment dance and performance dance., 3) Fine Arts in the form of paintings, drawings, sculptures, printmaking and artistic crafts, and 4) Dramatic Arts in the form of traditional drama and modern drama.